2021
DOI: 10.1002/slct.202101295
|View full text |Cite
|
Sign up to set email alerts
|

Route‐Optimized Synthesis of Bagasse‐Derived Hierarchical Activated Carbon for Maximizing Volatile Organic Compound (VOC) Adsorption Capture Properties

Abstract: The deep exploration of adsorption preferential specific structural properties of waste biomass‐derived activated carbon(AC) adsorbent is significant but challenged in the light of the synthetic control. This work optimizes chemical activation routine of waste bagasse‐derived AC to fabricate high‐performance adsorbent. The resultant optimal AC affords outstanding structural properties (SBET=2832.2 m2 g−1, SLang=5478.3 m2 g−1, Vtotal=1.93 cm3 g−1). The pre‐carbonization method (using high‐temperature calcinatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 48 publications
(42 reference statements)
0
4
0
Order By: Relevance
“…[ 40 ] It is also found that the Q st of methanol decreased with the increase of adsorption, illustrating that the interaction between methanol and UiO‐66‐NA@PDMS/MCE decreased gradually due to the multilayer adsorption effect. [ 41 ]…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…[ 40 ] It is also found that the Q st of methanol decreased with the increase of adsorption, illustrating that the interaction between methanol and UiO‐66‐NA@PDMS/MCE decreased gradually due to the multilayer adsorption effect. [ 41 ]…”
Section: Resultsmentioning
confidence: 99%
“…[40] It is also found that the Q st of methanol decreased with the increase of adsorption, illustrating that the interaction between methanol and UiO-66-NA@PDMS/MCE decreased gradually due to the multilayer adsorption effect. [41] The interaction between VOCs and UiO-66-NA@PDMS/MCE can be analyzed from three aspects (Figure 6a), including the open metal sites on MOFs, the functional groups on the MOFs and/or polymers via mutual interactions, and MOF nanocrystals via electrostatic interactions. [42] Especially, UiO-66-NA@PDMS/MCE produced extensive adsorption capacity also due to its inherent porosity of 65.3% (Table S2, Supporting Information) for adsorbing VOCs, and the chemical functional groups encompassed within the UiO-66-NA@PDMS/MCE show a profound influence over the adsorption of VOCs.…”
Section: Adsorption Performance Of Uio-66-na@pdms/mce To Vocsmentioning
confidence: 99%
“…[6] The efficient detection and elimination of HCHO molecules remains a great challenge. [7,8] Several cleaner strategies have been used for HCHO elimination, including physical adsorption, [9,10] photocatalysis, [11] and thermocatalytic oxidation. [12,13] Thermocatalytic oxidation technology is especially fit to purify industrial waste gas with the temperatures around 200 °C.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, a lot of research has focused on optimizing the preparation process of activated carbon to improve VOCs adsorption capacity. Yang et al (2021) studied the effect of the chemical activation process on the adsorption capacity of VOCs by properly adjusting the pre-carbonization method and the injection method of KOH. Zhu et al (2018) prepared activated carbon from corncob waste residue and studied the effects of carbonization temperature, impregnation ratio, and carbonization time on the structure and chemical properties of activated carbon.…”
Section: Introductionmentioning
confidence: 99%